Microservice-Based Architecture Optimization and Multi-layer Security Model for Green Mine Information Systems in Resource-Based Regions - Zhao, Wei; Ma, Guodong; Zhang, Yu; Yun, Qicheng; Bai, Hongxi; Zheng, Zhenhua; Zhang, Dexin (Informatica, 2026)
The construction of green mines in resource-based regions requires information systems that are highly concurrent, scalable, and secure. To address the limitations of existing systems—such as insufficient data processing performance, poor scalability, and weak protection capabilities—this study proposes a microservice-based architecture optimization and a multi-layer security model. The architecture adopts hierarchical design with microservices and containerization for modular deployment and elastic scalability, while a batch-stream integrated framework improves real-time and historical data processing. An improved Particle Swarm Optimization (PSO) algorithm is applied for computing resource scheduling, significantly reducing task completion time under high concurrency. In the security domain, a multi-layer model combining AES-256 encryption, access control, and an LSTM-based anomaly detection mechanism enables dynamic risk assessment and rapid response to threats. Experimental results demonstrate that the optimized system increases throughput by more than 30%, reduces average response time by over 25%, improves task completion rate to above 95%, enhances threat detection accuracy by around 15%, and raises defense success rate by over 12% compared with baseline systems. These findings confirm that the proposed framework provides an effective, secure, and scalable solution to support the green, intelligent, and safe development of mine production in resource-based areas.